The Role of Ethnoecology in Environmental Protection - Murtoz Usmonov (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The purpose of this research is to analyze the role of ethnoecology in environmental protection and to explore how traditional ecological values can contribute to modern sustainability efforts in the context of New Uzbekistan. This study employs a qualitative descriptive method through an extensive literature review of historical, cultural, and religious sources such as Avesta, the Qur’an, Hadiths, and classical works of Central Asian scholars. The research reveals that ethnoecology—integrating traditional knowledge and ecological awareness—serves as a moral and cultural foundation for promoting environmental protection. The findings highlight that the ecological consciousness deeply rooted in ancient Uzbek traditions demonstrates a sustainable human–nature relationship that aligns with contemporary ecological principles. It concludes that incorporating ethnoecological values into modern environmental policies can enhance ecological culture, strengthen public responsibility toward nature, and support sustainable development.